A novel stochastic calculation scheme for dynamic response analysis of FG-GPLRC plate subject to a moving load - Zhang, Xuebing; Chen, Baikuang; Shao, Zhanjun; Wang, Qingshan; Xiang, Ping (Acta mechanica, 2024)
This paper is the first attempt, to the best of the authors' knowledge, to explore the effect of the stochastic material parameters on the dynamic response of functionally graded graphene platelets reinforced composites plate subject to a moving load. A novel stochastic calculation scheme is presented in this study, which considers the spatial variability of structural material parameters for a more precise and effective analysis of plate structures. Using the radial point interpolation method (RPIM), the governing equations of the plate are derived based on the first-order shear deformation theory and Hamilton’s principle. The elastic moduli of the graphene platelets (GPLs) and the matrix are modeled as separate random fields, which are discretized using the Karhunen–Loève expansion (KLE) method. The random variables obtained by KLE were utilized in conjunction with the improved point estimation method (PEM) and Newmark- β method to determine the stochastic dynamic response. By comparing the results with those obtained using Monte Carlo method, the correctness and effectiveness of the proposed stochastic calculation scheme of PEM-RPIM are confirmed. Subsequently, the scheme was used to compute the coefficient of variation of the maximum dynamic deflection at the center of the plate, and also the sensitivity analysis was conducted. The results indicate that the distribution pattern and the weight fraction of GPLs have an impact on deflection sensitivity. Moreover, the deflection sensitivity is found to be significantly higher in response to variations of the random field E GPL .